CONSTRUCTION OF EVACUATION LINE-BY-PASS ALAI. - ADHA SAM, ANDRE AGASSI (Pendidikan Sosiologi, 2014)
The background of this research because of Padang is a disaster-prone cities, potential disaster occurred in Padang consists of earthquakes, tsunamis, floods, flooding, landslides, fires, coastal erosion and others. Anticipating that the government made evacuation route Padang (escape road). The evacuation route is divided into 6 sectors of the park area near the coast, heading away from the beach area. Line-By-Pass Alai entered into four sectors, is in accordance with the Local Government Regulation No. 4/2012 on spatial planning Padang 2012-2013. The phenomenon of the difficulty of compensation which has been ongoing since 2003, then this raises the interest of researchers to investigate because if the calculated mean restitution process has been going on for 11 years (2003-2014), the process is still not finished. The purpose of this study describe the constraint-alai building evacuation route Kuranji By Pass District of Padang. The theory used is the theory Dahrendrof conflict theory, this research approach is qualitative descriptive study to develop the type of problem under study, and subjects taken purposive sampling. totaling 13 informants study. The technique of collecting data through observation, interviews, document study. The data analysis techniques as in the descriptive type 1). Data collection, 2). Data reduction, 3). Presentation of data, 4). Conclusion. Location of the study was conducted in the Alai-By-Pass Kuranji District of Padang. Based on the results obtained the following conclusions: The development constraints caused by: (1) There is no definite price in damages buildings and crops affected by this development. (2) Residents sue their building price must be equal to other citizens banguanan. (3) Lack of socialization of the government to the citizens in the determination of the price of the building and the plant will be compensated as a result of this pembanguanan. Resulting in 2003 only a few plants and buildings that can be compensated by the government of Padang because there are many people who refuse the evacuation line construction Alai-By Pass.